Analysis of P5 Activities as the Implementation of Differentiated Learning in the Merdeka Curriculum in Elementary School - Selma Deah Permadani; Alik Mustafidal Laili (International Journal of Educational and Life Sciences, 2024)
In the independent curriculum, students carry out projects like the Strengthening Pancasila Student Profile (P5) Project, allowing them to independently explore and develop skills. This study aims to: 1) Analyze the P5 Project's impact on fourth-grade students at SD Negeri Samir; and 2) Evaluate differentiated learning in the independent curriculum for the same grade at SD Negeri Samir. This qualitative research involved 15 participants—facilitator teachers and 14 fourth-grade students (8 boys, 6 girls). Data was collected through observation, interviews, and documentation. Findings show: 1) P5 activities, from preparation to evaluation, were structured and successful; and 2) Differentiated learning effectively differentiated content and products, supported students, and maintained consistent analysis and evaluation.